University students' reliance on social media as a source of information on the emerging coronavirus, COVID-19 An exploratory study on a sample of Tishreen University students - الشعراوي, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study deals with the extent to which Tishreen University students rely on social media as a source of information on the emerging corona virus, COVID-19, through the rate of their daily use of those means, the motives behind this use, the nature of the information they track, the benefits and impacts achieved from that, and the degree of confidence in its credibility, It aims to achieve a major goal represented in knowing the degree of reliance of Tishreen University students on social media as a source of information related to the emerging corona virus, assuming that there is a positive statistically significant relationship between their exposure to social media and the degree of confidence in the information and news about the emerging Corona virus that it publishes, The study belongs to a group of descriptive research based on the survey method, and a simple random sample of 100 students was conducted during the period from 1/6/2020 until 6/15/2020. The results of the following were: that the intensity of the study sample's exposure to social media in general was medium, and low in terms of obtaining information and news about the emerging corona virus, and the high extent of the students of Tishreen University relying the study sample on social media to provide information about Corona virus, the nature of information, and news Related to the emerging corona virus, and that the benefits and effects achieved from their reliance on social media about the emerging corona virus were medium, and that the most common social media methods used by the students are: "Facebook", then WhatsApp, and at lower rates than the average Telegram, and at lower rates for Instagram and Twitter. The study also demonstrated the validity of the hypothesis that there is a positive direct correlation with statistical significance between the intensity of exposure to social media when searching for information and news about Corona virus, and confidence in the sources that publish That information and news; Where the severity of the association was moderate.